2000
DOI: 10.1046/j.1365-8711.2000.03204.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of metal abundances of the intracluster medium in the central region of clusters

Abstract: We measured metal abundances of the intracluster medium in the central regions of 34 nearby clusters of galaxies, using ASCA data. Clusters that have a sharp X‐ray emission centred on a cD galaxy are commonly found to exhibit a central increment in the Fe abundance, which is more pronounced in lower temperature clusters; +(0.1–0.2) solar at kT>5 keV, compared with +(0.2–0.3) solar at 1.5 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 41 publications
11
71
0
Order By: Relevance
“…It shows high values between 0.6 and 0.8 (in solar units) in the innermost 100 kpc, then varies between 0.2 and 0.5 at larger radii. The mean emission-weighted metallicity within 200 arcsec is about 0.4 Z , a value usually found in nearby rich clusters (e.g., Fukazawa et al 2000). The extent to which the hydrogen column density is fixed or not only has a very small effect; therefore, the results related to the metallicity presented below are always obtained by letting N H remain free.…”
Section: X-ray Spectral Analysis and Temperature Mapmentioning
confidence: 76%
“…It shows high values between 0.6 and 0.8 (in solar units) in the innermost 100 kpc, then varies between 0.2 and 0.5 at larger radii. The mean emission-weighted metallicity within 200 arcsec is about 0.4 Z , a value usually found in nearby rich clusters (e.g., Fukazawa et al 2000). The extent to which the hydrogen column density is fixed or not only has a very small effect; therefore, the results related to the metallicity presented below are always obtained by letting N H remain free.…”
Section: X-ray Spectral Analysis and Temperature Mapmentioning
confidence: 76%
“…Within cool core regions, clusters have negative abundance gradients (e.g. Fukazawa et al 2000;De Grandi et al 2004). and Leccardi et al (2010) also found central metal abundance excess in low-entropy core systems.…”
Section: Fe Profiles Within the Cool Core Regionsmentioning
confidence: 99%
“…The ASCA satellite (Tanaka et al 1994) first enabled us to measure the distribution of Fe in the ICM (e.g., Fukazawa et al 2000;Finoguenov et al 2000Finoguenov et al , 2001. The Fe abundances of these clusters are 0.2−0.3 solar, adopting the solar abundance from the "photospheric" values given by Anders & Grevesse (1989).…”
Section: Introductionmentioning
confidence: 99%
“…We leave the abundances of Ar, Ca, Fe, and Ni (the only elements that have emission lines in the range 3-10 keV) free and keep all the other abundances fixed to half the solar values [Fukazawa et al 2000; this corresponds for example to the 1T (3-10 keV) model in Tables 1 and 2].…”
Section: Observation and Data Preparationmentioning
confidence: 99%